The "I'm Healthy and Free of Anemia" Video in Improving Teenagers' Anemia Awareness - Kumalasari, Intan; Wulanda, Ayu Febri; Umar, Hermita Bus; Jaya, Herawati (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Anemia remains a major nutritional problem in developing countries, including Indonesia, largely due to adolescents’ limited nutritional knowledge. This study evaluated the effectiveness of the educational video “I’m Healthy and Free of Anemia” in improving adolescents’ knowledge and attitudes toward anemia. Using a quasi-experimental one-group pretest–posttest design, 140 students from SMA Muhammadiyah 1 Padang and SMA Muhammadiyah 2 Palembang were selected purposively. Data were collected through validated questionnaires and analyzed using the Wilcoxon Signed Rank Test. Results showed significant improvements in knowledge and attitudes after the intervention (p-value<0,001), with mean knowledge scores increasing from 70,11 to 81,14 and attitude scores from 76,14 to 82,73. The video was effective due to its engaging visual and audio elements, as well as practical examples. This study highlights the value of interactive educational media in enhancing adolescents’ awareness and understanding of anemia.